Building Trust in Generics and Biosimilar: Strengthening Regulatory Confidence - Abu Hassan, Mohammad Sharif; Emran, Farshila; Syed Mohthar, Sharifah Fauziyah; Ab Rahim, Roziana; Ab Hamid, Amielia (Malaysian Journal of Medical Sciences, 2025)
This article discusses the crucial role of traditional small-molecule generic drugs and biosimilar medicines in enhancing healthcare accessibility, particularly in lower- and middle-income countries such as Malaysia. It highlights how Malaysia’s evolving regulatory science, supported by the Drug Control Authority (DCA) and the National Pharmaceutical Regulatory Agency (NPRA), fosters an environment where quality, safety, efficacy, and affordability converge, aligning with national healthcare goals. Hanan Regulatory Services Sdn. Bhd. (HRS), the regulatory arm of the Hanan Group of Companies, upholds rigorous standards for product registration, bio?equivalence testing, manufacturing audits, pharmacovigilance and training. Malaysia’s regulatory framework requires the actual measured difference in bioavailability between the generic and innovator products to be on average, extremely small — approximately 3.5% only. These measures, along with post?marketing surveillance and good manufacturing practice, address misconceptions about generics, emphasising that their lower price does not equate to inferior quality.On 4 March 2025, HRS registered Rapilin 30, Malaysia’s first premixed insulin aspart biosimilar, reflecting the growing industry maturity. In the United States, generics and biosimilars generated an estimated USD 467 billion in savings in 2024, demonstrating the economic potential of such medicines. Malaysia’s continued adherence to international regulatory standards and collaboration between public and private sectors will be key to sustaining confidence, achieving national pharmaceutical self?reliance and medicine security.